1987
DOI: 10.1212/wnl.37.4.715
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of amyotrophic lateral sclerosis with the TRH analog DN‐1417

Abstract: Thyrotropin-releasing hormone has been reported to increase strength in patients with amyotrophic lateral sclerosis (ALS). DN-1417 is an analog of thyrotropin-releasing hormone, which has less endocrinologic activity, but more anterior horn cell stimulating effect (with no "autorefractory state"). However, 2 mg DN-1417, IM twice a day for 1 month in an open-label trial, produced no objective improvement of strength in nine patients with ALS. No patient entered the double-blind, placebo-controlled phase of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The effects of RX77368 or other TRH analogues on cardiovascular measures in humans have not previously been reported, except for comments noting little effect or transient hypertension in neurological patients [22][23][24]. We have found that RX77368 produced a pressor response which was prolonged in comparison with that of TRH, consistent with its known resistance to metabolic degradation.…”
Section: Discussionsupporting
confidence: 70%
“…The effects of RX77368 or other TRH analogues on cardiovascular measures in humans have not previously been reported, except for comments noting little effect or transient hypertension in neurological patients [22][23][24]. We have found that RX77368 produced a pressor response which was prolonged in comparison with that of TRH, consistent with its known resistance to metabolic degradation.…”
Section: Discussionsupporting
confidence: 70%
“…TRH mimetics have been shown to be useful in the treatment of spinocerebellar degeneration ( Shimizu et al, 2020 ; Ijiro et al, 2022 ), amyotrophic lateral sclerosis ( Hawley et al, 1987 ), spinal muscular atrophy ( Kat o et al, 2009 ), prolonged disturbance of consciousness due to aneurysmal subarachnoid hemorrhage ( Shibata et al, 2019 ), Parkinson’s disease ( Zheng et al, 2018a ; Zheng et al, 2018b ), epilepsy ( Rajput et al, 2009 ; Sah et al, 2011 ), psychiatric disorders with underlying inflammatory processes ( Kamath, 2012 ), and possibly depression ( Duval et al, 2021 ). The effects of TRH and its analogs on the CNS are usually achieved in cooperation with the modulatory effects of neurotransmitters such as glutamate, dopamine, norepinephrine, acetylcholine, serotonin, or GABA.…”
Section: Thyrotropin-releasing Hormone Receptor Ligands and Their Pha...mentioning
confidence: 99%
“…TRH has been tested in a larger number of clinical trials, but none of them showed a benefit in ALS patients (Brooke et al, 1986;Brooks et al, 1987;Caroscio et al, 1986;Congia et al, 1991;Hawley et al, 1987;Imoto et al, 1984;Klimek et al, 1989;Klimek et al, 1988;Miller & Warnick, 1989;Mitsumoto et al, 1986;Munsat et al, 1992;Patrignani et al, 1992;Serratrice et al, 1985;Stober et al, 1985;Thielen et al, 1987;Yamane et al, 1986).…”
Section: Thyreotropin Releasing Hormone (Trh Protirelin)mentioning
confidence: 99%